EFL teachers’ beliefs and practices about digital learning of English - Arif Nugroho; Ira Mutiaraningrum (EduLite: Journal of English Education, Literature and Culture, 2020)
The last two decades have been the witness of many studies reporting the disparity between EFL teachers’ beliefs and practices in technology integration around the world. Notwithstanding the enormous studies on EFL teachers’ beliefs and perceptions of digital technology use for language classroom, the literature has still been silent on the relation between Indonesian EFL teachers’ beliefs and practices. The present study thus sheds some light on 15 EFL teachers’ beliefs and practices about digital learning of English in Indonesia. Drawing on data from the written reflections and semi-structured interviews, the findings revealed that these EFL teachers were well equipped with the importance and objective of teaching English by means of digital devices, but appeared hesitant and lacked of preparation in their teaching practices. The semi-structured interview further depicted that their unconfident and lack of preparation was not only a result of inadequate training but also of limited resources and digital facilitation. The institutional supports influenced by environmental readiness also affected their efficacy for digital learning of English. The findings contribute to the realm of English language teaching with regards to offering literature of EFL teachers’ professional development.